Normative data for the digit–letter substitution task in school children - Pradhan, Balaram (Medknow Publications, 2009)
BACKGROUND/AIMS: To establish the norms for the substitution task, a measure of psychomotor performance. MATERIALS AND METHODS: Eight hundred and forty three school students were selected in the present study aged between 9-16 years (mean age = 12.14; SD = 1.77). Subjects were assessed one at a time for Digit-Letter Substitution Task (DLST). RESULTS: Both age and sex influenced performance on the DLST; therefore, correction scores were obtained on the basis of these factors. CONCLUSIONS: The availability of the Indian normative data for the DLST will allow wider application of this test in clinical practice.